The Role of Cooperative Reputation in Moderating Relationship Levels of Deposit Rates and Financial Literacy to Members' Saving Decisions - I Komang Alit Anggara Wijaya Kusuma; I Gede Putu Kawiana; A.A Ngurah Gede Sadiartha (Management and Applied Social Studies Review, 2023)
Purpose – The purpose of this study was to analyze the role of cooperative reputation in moderating the relationship between deposit interest rates and financial literacy in saving decisions of members of provincial savings and loan cooperatives in Bali Province. Methodology – The research population is all members of provincial savings and loan cooperatives in Bali Province. The sampling technique was carried out by stratified proportion sampling. Questionnaires that have been tested for validity and reliability are given to 100 respondents. The data analysis method used was descriptive analysis and inferential analysis with Structural Equation Model-Partial Least Square (SEM-PLS) analysis Findings – The results showed that the variable deposit interest rates and financial literacy had a positive and significant influence on member savings decisions. Cooperative reputation has a positive but insignificant moderating role between deposit interest rates and financial literacy on member savings decisions. Cooperative reputation tends to be a predictor (directly influencing) the savings decisions of members of provincial savings and loan cooperatives in Bali Province. The implication of the research is that cooperatives need to pay attention to providing deposit interest rates, member financial literacy, and cooperative reputation to increase member savings decisions. The research suggestion is that cooperatives provide moderate interest rates, improve the financial literacy of members and administrators, and improve the reputation of cooperatives. Originality – Cooperative reputation has a positive but insignificant moderating role between deposit interest rates and financial literacy on member savings decisions.